MS Teams in umetna inteligenca kot digitalna podpora pri poučevanju bralnega razumevanja v 3. razredu - Ivačič, David (Revija inovativna pedagogika, 2025)
This paper aims to present the use of artificial intelligence (AI) to assist Grade 3 pupils whose first language is not Slovenian. The key challenge is to improve their reading comprehension, which is fundamental for successful learning across all subjects. The case study highlights the importance of technology in promoting inclusive and individualized learning. The planning was guided by the current curriculum and the DigiComp 2.2 and DigCompEdu frameworks, which are adapted for developing digital competencies in early primary education. The focus is on skills such as basic use of digital tools, understanding interactive content, and safe technology use while also emphasizing the importance of developing teachers' competencies for creating digitally supported learning activities. Several challenges in this approach are also highlighted. The methodological approach is based on using the MS Teams platform and applications such as Learning Accelerators, Reading Progress, Forms, Insights, and Reflect. With the help of Reading Progress and AI, individualized tasks were designed to improve reading and text comprehension. The platform enables automated reading analysis, pronunciation recognition, and progress tracking. Forms was used to create interactive quizzes and tasks that supported reading comprehension assessment and reinforced language skills. Insights and Reflect provided insights into pupils’ work and facilitated feedback. The results include improved reading and language skills, greater confidence in using the Slovenian language, and broader adoption of the described methods for working with pupils facing similar challenges.
Keywords: bralno razumevanje; Digitalna pismenost; individualizacija; individualization; Informacijsko-komunikacijska tehnologija; jezikovne zmožnosti; language competencies; MS Teams; Osnovnošolsko izobraževanje; reading comprehension; Umetna inteligenca